PREDICTING AVERAGE MARKS IN TERTIARY EDUCATION USING COGNITIVE TESTING AND SECONDARY EDUCATION PERFORMANCE - Opperman, Ingrid; Greyling, Michael (New Voices in Psychology, 2016)
South Africa faces several challenges in higher education including numbers of graduates following drives for mass participation. This is a complex problem of which selections are one component. This institution uses the PIBSpEEx as an adjunct to grade 12 results in selections. The predictive power of this instrument and secondary schooling results was investigated in relation to ‘success’ in the form of average marks as well as a pass-fail model. Results indicated statistical significance for secondary schooling and sub-tests of the PIBSpEEx although effect sizes were not as expected given international research. This questions which aspects of cognition, education and selection procedures should be considered to select students with a higher likelihood of success in the South African context.